A damage evolution rate controlled method for catastrophic failure process of metal films. (September 2021) - Sun, Bin; Huang, Xingzhen; Xu, Zhaodong
Abstract: In order to improve material damage and fracture band prediction accuracy based on framework of continuum damage mechanics, a damage evolution rate controlled continuum damage mechanics simulation algorithm is developed to simulate material failure process from damage initiation to fracture. The advantage of the algorithm is used to handle and control the damage evolution rate based on the average strain, which is used for considering the stress redistribution better during the simulation of the competitive and coupling fracture process. Compared to regularization of the fracture or damage process in the strain-gradient theory, the developed algorithm is only to handle the scalar such as the damage value instead of dealing with the tensor such as the strain gradient, which can overcome complicated derivation due to the fact that high-order gradient of strain is coupled in the constitutive relation. In order to study the failure mechanisms of metal films and verify effectiveness of the developed algorithm, catastrophic failure process of two copper film specimens, were simulated and compared with the simulation results obtained from conventional continuum damage mechanics simulation method without the developed algorithm and experimental results. The results show that the developed algorithm is effective to simulate damage and fracture process of metal films for studying their failure mechanisms, which can obtain more relatively accurate damage and fracture band prediction results. Highlights: An algorithm is developed to simulate damage and fracture process of metal films. Competitive and coupling material failure process can be considered. More relatively accurate damage and fracture band prediction results can be obtained. The effectiveness of the algorithm is verified by comparing with experimental results.